MIXED INFECTION IN A DONKEY: A CASE REPORT - Selvam, A; Sekar, M; Venkataraman, K S; Gowri, B; Krishna, Mahesh; Suresh, R V (Indian Journal of Veterinary Sciences and Biotechnology, 2009)
A five-month-old male donkey was presented to the large animal clinic, out patient medical unit, Madras Veterinary College Teaching Hospital with history of not drinking milk for past two days and symptoms of dull, dehydrated and watery diarrhoea with foul smelling. Strongyle spp eggs were detected on faecal examination and the bacteriological culture of the sample revealed Salmonella spp and the diagnosis was confirmed as mixed infection. Antibiotic sensitivity test, indicated that Salmonella isolates were sensitive to Ceftriaxone and tetracycline. This type of rare mixed infection with strongylosis and salmonellosis was successfully treated with antibiotics, dewormer and fluids.
Keywords: Donkey; Strongyle; Salmonella; Mixed infection and Diagnosis